Willingness to pay for biodiversity conservation and well-being in Bako National Park, Sarawak, Malaysia - Ibrahim, Mohamad Syahrul Nizam; Johari, Shazali; Md Allwi, Norul Izani; Hassan, Suziana (Association for Researcher of Skills and Vocational Training, 2023)
Bako National Park (BNP) is Sarawak's oldest and smallest protected area which has high biodiversityconservation value which critical to policy development. The economic valuation using contingent valuation method(CVM) is crucial to estimate non-marketed goods which refer to public willingness to pay (WTP) for conservationefforts in the area. WTP refers to the amount of money a person is willing and able to spend on recreational activitieswhich reflects their awareness towards biodiversity conservation in BNP. Both local community and visitors play animportant role in the development of sustainable tourism and human well-being. Thus, the study elucidates thewillingness to pay of local community and visitors for conserving biodiversity in BNP. Specifically, the studyattempts to look at the maximum price they are willing to pay for a park entrance fee and how it relates to communitywell-being in the area. The validated questionnaire was distributed to the visitors and local community by simplerandom sampling technique. Consequently, the maximum price of visitors and local community willingness to payfor biodiversity conservation was MYR100 and MYR50, respectively. Although the prices varied due to theirsociodemographic, it still possessed that their willingness to support conservation efforts is in good shape. Thecommunity well-being (CWB) constructed indicated a good mean through the dimensions of environment (3.70),neighborhood (3.65), life and social relation (3.92), services and facilities (3.33), education (3.50), economics (3.25)and cultures (3.50). A good level of WTP reflected their awareness of the importance of national park as a key entityin ensuring their well-being through its dimensions. Therefore, it is crucial to understand the challenges faced at thebottom level in the effort towards holistic biodiversity conservation.